2002
DOI: 10.1007/s00122-002-1169-9
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity impacts of forest fires, forest harvesting, and alternative reforestation practices in black spruce (Picea mariana)

Abstract: Benchmarks were established for genetic diversity inherent in natural mature populations, and genetic diversity impacts of forest fires, clearcut harvesting and alternative natural and artificial silvicultural regeneration practices were determined in black spruce (Picea mariana). Allozymes of 32 loci were used to determine and compare genetic diversity and genetic relationships of adjacent or nearby four stand types: post-fire natural mature (FNM), post-fire natural young (FNR), post-harvest natural young (HN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
35
0
6

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(48 citation statements)
references
References 27 publications
7
35
0
6
Order By: Relevance
“…Vettori et al [34] observed a similar situation when studying the geographic distribution of chloroplast variation in Italian populations of beech. In general, the population genetic structure of P. asperata seems to resemble that observed in P. strobes [3] and P. mariana [35]. Fig.…”
Section: Discussionsupporting
confidence: 53%
“…Vettori et al [34] observed a similar situation when studying the geographic distribution of chloroplast variation in Italian populations of beech. In general, the population genetic structure of P. asperata seems to resemble that observed in P. strobes [3] and P. mariana [35]. Fig.…”
Section: Discussionsupporting
confidence: 53%
“…This usually determines a time lag before the consequences of disturbances, such as habitat fragmentation or exploitation, can be detected (Kramer et al, 2008). In fact, several studies did not find any reduction in genetic diversity or changes in the mating systems of wind-pollinated temperate species following silvicultural practices (for example, Rajora and Pluhar, 2003;Robledo-Arnuncio et al, 2004). However, evidence that silvicultural treatments may modify within-stand genetic structure exists (Rajora, 1999;Rajora et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Genetic diversity within tree populations may confer superiority in individual fitness and a buffer against pressure from environmental change (Lambeth and McCullough 1997;Mosseler et al 2003;Rajora and Pluhar 2003;González-Martínez et al 2006). Maintenance of adequate genetic diversity in forest trees not only plays a decisive role in species persistence, but also has an important influence on the continuity of forest regeneration and succession (Newton et al 1999;Booth and Grime 2003;Navascués and Emerson 2007).…”
Section: Introductionmentioning
confidence: 99%